Trichogin GA IV Alignment and Oligomerization in Phospholipid Bilayers. (17th July 2019) - Salnikov, Evgeniy S.; De Zotti, Marta; Bobone, Sara; Mazzuca, Claudia; Raya, Jesus; Siano, Alvaro S.; Peggion, Cristina; Toniolo, Claudio; Stella, Lorenzo; Bechinger, Burkhard
Abstract: Trichogin GA IV is a short peptaibol with antimicrobial activity. This uncharged, but amphipathic, sequence is aligned at the membrane interface and undergoes a transition to an aggregated state that inserts more deeply into the membrane, an assembly that predominates at a peptide‐to‐lipid ratio (P/L) of 1:20. In this work, the natural trichogin sequence was prepared and reconstituted into oriented lipid bilayers. The 15 N NMR chemical shift is indicative of a well‐defined alignment of the peptide parallel to the membrane surface at P/Ls of 1:120 and 1:20. When the P/L is increased to 1:8, an additional peptide topology is observed that is indicative of a heterogeneous orientation, with helix alignments ranging from around the magic angle to perfectly in‐plane. The topological preference of the trichogin helix for an orientation parallel to the membrane surface was confirmed by attenuated total reflection FTIR spectroscopy. Furthermore, 19 F CODEX experiments were performed on a trichogin sequence with 19 F‐Phe at position 10. The CODEX decay is in agreement with a tetrameric complex, in which the 19 F sites are about 9–9.5 Å apart. Thus, a model emerges in which the monomeric peptide aligns along the membrane surface. When the peptide concentration increases, first dimeric and then tetrameric assemblies form, made up from helices oriented predominantly parallel to the membrane surface. The formation of these aggregates correlates with the release of vesicle contents including relatively large molecules. Abstract : Line up : The membrane interactions and structure of the natural antimicrobial peptide trichogin GA IV have been investigated by CD, ATR FTIR and solid‐state NMR spectroscopy. A model emerges in which the peptide preferentially aligns parallel to the membrane surface and forms dimeric and tetrameric assemblies at higher concentrations.